Analisis Preferensi Mahasiswa STIS Berdasarkan Akun Facebook yang Dimiliki - Takdir -; Choerul Afifanto (Jurnal Aplikasi Statistika & Komputasi Statistik, 2015)
Currently, social media is used massively in various societies. Facebook is one of the greatest social media in terms of total and frequency of uses, as well as the number of collected information, especially the information about relationships between entities. This study identifies preference of active STIS’s students based on their Facebook account. Their Facebook accounts are collected from their Facebook group communities. The preference data are collected by crawling the liked pages and joined groups. The results of this study are the characteristics view of students’ preferences in form of statistics of interesting topic types and visualization of students’ clusters for certain topics. Approaches used in this research to extract and analyze data in social media could become a reference for another research fields which use social media data.